Tough talk, tougher targets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
With the Cotonou Agreement having to be shoe-horned into the rules of the World Trade Organisation (WTO), it s hard for ACP countries to know which way to turn. They have to unravel complex topics, forge negotiating strategies and harmonise their...